Reverse Direction Transmission in Wireless Networks: Review - Milad, Ali Ahmad; Muhamad Noh, Zul Azri; Shibghatullah, Abdul Samad; Algaet, Mustafa Almahdi (2013)
Reverse direction mechanism is a promising significant development that may lead to promoting the accuracy of TXOP. The transfer, in conventional TXOP operation, is one way direction out of the station which holds the TXOP and which is not applied to some network services using two lane traffic namely VoIP and on-line gaming. Therefore, the conventional TXOP operation enhances only the forward direction transfer, but not the reverse direction transfer. Moreover, reverse direction mechanism makes it possible for the holder of TXOP to reserve unused TXOP time for its receivers which may improve the channel utilization as well as the performance of reverse direction traffic flows. It is well-known that the reverse direction transfer scheme aims mainly to improve the effectiveness and that plays a key role in reducing the overhead and increasing the system throughput. Thus, this paper provides an overview of a research progress in reverse direction transmission scheme over high speed wireless LANs. Moreover, it addresses the reverse direction mechanism that has been proposed for the next generation wireless networks and the ones adopted by IEEE 802.11n standard. Furthermore, it stresses the reverse issues that require to be dealt with in order to bring further progress to the reverse direction transmission.